Estimation of concentration of chlorophyll, N, and biomass using non-destructive measurements in arugula (Eruca sativa) (Bioagro, 2022)
Nitrogen is an essential nutrient for plants and the most required element in leafy vegetables. The objective of this research was to estimate the concentration of chlorophyll, of nitrogen and fresh biomass by using non-destructive portable meters in arugula (Eruca sativa L.). The research was carried out in a greenhouse,  where  the treatments  were  five  levels  of  NO3-N  (0, 4, 8, 12  and  16 mEq·L-1) based on Steiner's nutrient solution. The evaluations were weekly for both greenhouse variables (fresh biomass, SPAD, atLEAF and MC-100 readings) and laboratory variables (chlorophyll and N concentrations). The results showed that the relationship between SPAD readings, nitrogen, chlorophyll and fresh matter were high, positive and significant, with correlation coefficients of 0.93 - 0.97; for atLEAF readings, similar relationships were observed, with correlation coefficients of 0.96-0.99. The relationships between SPAD, atLEAF, and MC-100 readings were also high, positive, and significant, with correlation coefficients from 0.97 to 0.98. This indicates that the SPAD, atLEAF and MC-100 meters are valid in-situ methods to estimate the nutritional status of chlorophyll and nitrogen in arugula cultivation under greenhouse conditions in a non-destructive, fast and accurate way.
Keywords: atLEAF; MC-100; leafy vegetable; plant nutrition; SPAD